Ethics and politics in the italian debate on realism (Balthazar, 2022)
Are reality and truth concepts to really worry about? How the italian debate concerning those terms have been proceeding in the last fifteen years? In this paper we try to answer these and other questions. In §1 we introduce the debate and its actors. In §2 we focus on the connections between the principal concepts of the discussion and we try to offer an interpretation that has the aim to highlight mainly what is at stake in terms of ethics and politics. In §3 we are giving a flavour of the proposed theories from each autor and we try to bring out the real motivations and purposes that underlie the different views. In the end, in §4, we draw conclusions about the validity and the worthness of the debate by highlighting what is common at the various positions and we try to connect the theorical debate with the actual critical situation of the public debate and the ethical and political concerns that are at stake.
Keywords: reality; truth; relativism; ethics; politics